Detection and differentiation of Brucella abortus and Brucella melitensis by multiplex real-time polymerase chain reaction in patients with pyrexia of unknown origin at a tertiary care centre in Northern India - Kumari, Renu; Kalyan, Raj Kumar; Gupta, Kamlesh Kumar; Verma, Sanjeev Kumar (International Journal of Research in Medical Sciences, 2025)
Background: Brucellosis is a neglected zoonotic disease caused by Brucella spp., posing serious public health and economic challenges, especially in low- and middle-income countries. The disease presents with nonspecific symptoms, and conventional diagnostic methods are often time-consuming and less accurate. Multiplex real-time polymerase chain reaction (m-RT PCR) has emerged as a rapid and reliable diagnostic tool for detecting and differentiating Brucella species. The prevalence, clinical characteristics, and risk factors of human brucellosis among patients with pyrexia of unknown origin (PUO) and to perform molecular characterization of Brucella species using m-RT PCR at King George’s Medical University, Lucknow. Methods: A total of 315 PUO patients were enrolled between January 2023 and March 2025. Blood samples were collected, sera separated, and DNA extracted using the QIAamp DNA Mini Kit. Multiplex RT-PCR assays targeting the bcsp31 and IS711 genes were performed with species-specific probes to detect Brucella spp., B. abortus, and B. melitensis. Clinical, demographic, and laboratory data were analyzed. Results: Out of 315 samples, 30 (9.5%) were positive by m-RT PCR-24 (80%) for B. abortus and 6 (20%) for B. melitensis. Most positive cases were adults (70%) and rural residents (73.3%), with housewives (33.3%) and students (26.7%) being the most affected. Conclusions: Human brucellosis is endemic in Uttar Pradesh, with B. abortus as the predominant species. M-RT-PCR offers a rapid, sensitive, and specific diagnostic method, emphasizing the need for public awareness and a One Health approach for effective control.